Thermal Assessment of a Novel Thermal Diode Solar Water Heater Using Different Heat Transfer Fluids: An Experimental Study - H. Farzan (Iranica Journal of Energy and Environment)
Thermal diode solar water heaters (SWHs) are novel, promising tools that address an inherent problem in SWHs: significant heat losses. Thermal diodes SWHs use heat transfer fluids (HTFs) to carry out this crucial task, or in other words, to improve the heat transfer rate during the collection period and reduce its retention period. This study investigates how HTFs affect the performance of thermal diode SWHs. To this aim, a thermal diode SWH was fabricated and tested outdoors using two common HTFs: pure water and ethanol-water azeotrope. Ethanol-water azeotrope has a lower boiling point and latent heat than pure water; hence, it goes through the phase change process sooner and faster than pure water. The results reveal that the maximum reserved water temperature in the SWH using azeotrope is nearly 17.7% higher than in the SWH using pure water. Furthermore, the reserved water in the SWH using azeotrope loses its thermal energy in a gentler gradient than the water in the SWH using pure water during the retention period. The collection and retention efficiencies of the SWH using azeotrope are nearly 37.83% and 130.2% higher than those using pure water. Hence, ethanol-water azeotrope is a suitable material, serving as HTF in thermal diode SWHs.